Contextual Practice at SMKN 1 Kasongan, Central Kalimantan: Project-Based Learning for Arduino and IoT (Internet of Things) Based Water Pollution Mitigation - Rendi Indiwara (Yayasan Al-Afif, 2025)
This article describes the Project-Based Learning (PjBL) practice implemented at SMKN 1 Kasongan, Central Kalimantan, in the context of mitigating river water pollution caused by community activities and illegal mining. Using the PjBL approach, students created and used a water quality monitoring device that works with an ESP8266 microcontroller, TDS and temperature sensors, and an IoT application made with Blynk and AppSheet. This study used a qualitative descriptive method with data collected through observation, digital documentation, student reflection, and teacher formative assessment. The learning outcomes showed that students were able to develop a tool that functioned well in measuring and transmitting water quality data in real-time. In addition to improving technical skills, this project also strengthened 21st-century skills, namely critical thinking, creativity, collaboration, and communication. The local context raised made the learning more meaningful and built students' ecological awareness. Despite technical challenges and tool limitations, this learning succeeded in creating a solution-oriented, collaborative, and relevant learning ecosystem for the 21st century. This practice can be replicated and developed as an integrative contextual learning model in various educational units.